Democracy by force : U.S. military intervention in the post-Cold War world - Von Hippel, Karin (Cambridge ; New York : Cambridge University Press, 2000)
Study of US military interventions after the Cold War.
Introduction : dangerous hubris -- Invasion or intervention? Operation Just Cause -- Disappointed and defeated in Somalia -- Heartened in Haiti -- UNPROFOR, IFOR and SFOR : can peace be FORced on Bosnia? -- Hubris or progress : can democracy be forced?
Includes bibliographical references (pages 207-214) and index.
Print version record.
eBooks on EBSCOhost
Keywords: United States -- Foreign relations -- 1989-; Intervention (International law); Intervention (Droit international); États-Unis -- Relations extérieures -- 1989-; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Diplomatic relations; Intervention (International law); United States; Militaire interventie; Natievorming; Reconstructies; Verenigde Staten; Panama; Somalia; Haïti.; Bosnië; Since 1989; Electronic books; Electronic books